The genomic diversification of the whole Acinetobacter genus: origins, mechanisms, and consequences - Touchon, Marie; Cury, Jean; Yoon, Eun-Jeong; Krizova, Lenka; Cerqueira, Gustavo C; Murphy, Cheryl; Feldgarden, Michael; Wortman, Jennifer; Clermont, Dominique; Lambert, Thierry; Grillot-Courvalin, Catherine; Nemec, Alexandr; et al. (Genome biology and evolution, 2014)
Bacterial genomics has greatly expanded our understanding of microdiversification patterns within a species, but analyses at higher taxonomical levels are necessary to understand and predict the independent rise of pathogens in a genus. We have sampled, sequenced, and assessed the diversity of genomes of validly named and tentative species of the Acinetobacter genus, a clade including major nosocomial pathogens and biotechnologically important species. We inferred a robust global phylogeny and delimited several new putative species. The genus is very ancient and extremely diverse: Genomes of highly divergent species share more orthologs than certain strains within a species. We systematically characterized elements and mechanisms driving genome diversification, such as conjugative elements, insertion sequences, and natural transformation. We found many error-prone polymerases that may play a role in resistance to toxins, antibiotics, and in the generation of genetic variation. Surprisingly, temperate phages, poorly studied in Acinetobacter, were found to account for a significant fraction of most genomes. Accordingly, many genomes encode clustered regularly interspaced short palindromic repeats (CRISPR)-Cas systems with some of the largest CRISPR-arrays found so far in bacteria. Integrons are strongly overrepresented in Acinetobacter baumannii, which correlates with its frequent resistance to antibiotics. Our data suggest that A. baumannii arose from an ancient population bottleneck followed by population expansion under strong purifying selection. The outstanding diversification of the species occurred largely by horizontal transfer, including some allelic recombination, at specific hotspots preferentially located close to the replication terminus. Our work sets a quantitative basis to understand the diversification of Acinetobacter into emerging resistant and versatile pathogens.
Keywords: Clustered Regularly Interspaced Short Palindromic Repeats; bacterial genus; mobile genetic elements; Phylogeny; nosocomial pathogens; Acinetobacter; sekvence CRISPR; Genome, Bacterial; Interspersed Repetitive Sequences; genom bakteriální; comparative genomics; rozptýlené repetitivní sekvence; Genomics; evolution; fylogeneze; genomika